Recovery of the Basis of Group π2n Representation on its Subgroup πn×n and Harriman’s Theorem - Klimko, G.T. (Штучний інтелект, 2012)
The proof of Harriman’s theorem [1] is given for arbitrary order reduced density matrix of both the clear, and the mixed states of fermions at once. Its essential parts are a Pauli exclu- sion principle, rotation group symmetry of spin functions and new commutation relations. Теорема Гаррімана [1] доведена для редуцироних матриць густини чистого і змішаного станів ферміонів з використанням принципу Паулі, симетрії спінових функцій і нових наслідків, пов'язаних з переміщеннями штрихованих і нештрихованих змінних. Теорема Гарримана [1] доказана для редуцированных матриц плотности чистого и смешанного состояний фермионов из принципа Паули, симметрии спиновых функций, новых следствий из перестановок штрихованных и не штрихованных переменных.